1999
DOI: 10.1038/sj.onc.1203160
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of IκB kinase α and NF-κB in prostate cancer cells is inhibited by ibuprofen

Abstract: Apoptotic pathways controlled by the Rel/NF-kB family of transcription factors may regulate the response of cells to DNA damage. Here, we have examined the NFkB status of several prostate tumor cell lines. In the androgen-independent prostate tumor cells PC-3 and DU-145, the DNA-binding activity of NF-kB was constitutively activated and IkB-a levels were decreased. In contrast, the androgen-sensitive prostate tumor cell line LNCaP had low levels of NF-kB which were upregulated following exposure to cytokines o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
215
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(236 citation statements)
references
References 30 publications
18
215
0
3
Order By: Relevance
“…These reports together with the observed upregulation of IkBa in prostate cancer cells may provide a mechanism to explain the increased apoptosis and reduced tumour vascularity in prostate cancer specimens (Keledjian et al, 2001). Constitutive activation of NF-kB has been reported in many tumours (Baldwin, 1996), including androgen-independent prostate cancer cells (Pajonk et al, 1999;Palayoor et al, 1999;Suh et al, 2002) and oestrogen receptor-negative breast cancer cells (Biswas et al, 2001). This activation of NF-kB survival signalling is believed to provide a growth advantage in androgen-independent prostate cancer cells by suppressing apoptosis and inducing cell adhesion and angiogenic potential (Huang et al, 2001;Gasparian et al, 2002).…”
Section: Discussionmentioning
confidence: 72%
“…These reports together with the observed upregulation of IkBa in prostate cancer cells may provide a mechanism to explain the increased apoptosis and reduced tumour vascularity in prostate cancer specimens (Keledjian et al, 2001). Constitutive activation of NF-kB has been reported in many tumours (Baldwin, 1996), including androgen-independent prostate cancer cells (Pajonk et al, 1999;Palayoor et al, 1999;Suh et al, 2002) and oestrogen receptor-negative breast cancer cells (Biswas et al, 2001). This activation of NF-kB survival signalling is believed to provide a growth advantage in androgen-independent prostate cancer cells by suppressing apoptosis and inducing cell adhesion and angiogenic potential (Huang et al, 2001;Gasparian et al, 2002).…”
Section: Discussionmentioning
confidence: 72%
“…In addition to its role in prostate cancer behaviour (Andela et al, 2003), NF-kB activation is also implicated in chemo-and radioresistance. These observations are complemented by studies showing that NF-kB inhibition is a promising strategy for prostate cancer treatment, and, particularly, as a chemo-or radio-sensitisation strategy (Palayoor et al, 1999;Altuwaijri et al, 2003;Flynn et al, 2003;Kikuchi et al, 2003;Chendil et al, 2004). Clearly, inhibition of NF-kB may potentiate the antineoplastic effect of conventional chemotherapeutic agents (Sanchez-Perez et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Thus EPA, which prevents nuclear migration of NF-kB in murine myotubes in response to PIF by stabilising the cytosolic I-kB/NF-kB complex (Whitehouse and Tisdale, 2003), possibly by interfering with I-kB phosphorylation (Novak et al, 2003), has been shown to attenuate the development of further weight loss in weight-losing patients with pancreatic cancer (Wigmore et al, 2000) and produce an increase in lean body mass when combined with a high protein energy dense nutritional supplement (Barber et al, 1999). The anti-inflammatory agent, ibuprofen, has been shown to inhibit constitutive activation of NFkB and IKKa in prostate cancer cells (Palayoor et al, 1999), and when combined with megestrol acetate produced an increase in body weight in gastrointestinal cancer patients (McMillan et al, 1999), while megestrol acetate alone produced a decrease in body weight. Another anti-inflammatory agent, thalidomide, can also block NF-kB activation through inhibition of IKK (Keifer et al, 2001), and has been shown to promote weight gain in HIV-infected patients receiving treatment for tuberculosis (Reys-Teran et al, 1996), and is currently under evaluation for the treatment of cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%